Mydriatic insert and intracameral injections compared with mydriatic eyedrops in cataract surgery: Controlled studies. Issue 7 (July 2015) - Behndig, Anders; Korobelnik, Jean‐François
Abstract : N/A: Mydriatic eyedrops are the standard method for pupil dilation in cataract surgery, but their limitations have prompted a search for alternative techniques. Two alternatives—an ophthalmic insert containing phenylephrine and tropicamide and intracameral injections of various combinations of lidocaine, cyclopentolate, and phenylephrine, with or without epinephrine in the irrigating solution—have been assessed in prospective controlled studies, including randomized controlled trials (RCTs). We reviewed the safety and efficacy of mydriatic ophthalmic inserts and intracameral mydriatic injections compared with the safety and efficacy of mydriatic eyedrops using a systematic PubMed search (1963 to 2014). We identified 9 prospective studies (7 RCTs, 637 patients) of the mydriatic ophthalmic insert and 15 prospective studies (14 RCTs, 1020 patients) of intracameral mydriatic injections; 7 of the RCTs compared intracameral mydriatic injections and mydriatic eyedrops and 7 RCTs studied the optimum intracameral mydriatic injection protocol. The latter showed that a lidocaine and phenylephrine–based solution, without irrigating epinephrine, was optimum for intracameral mydriatic injections. The mydriatic ophthalmic insert and intracameral mydriatic injections were consistently shown to be safe and as effective as mydriatic eyedrops. Each method has distinct advantages and limitations. Financial Disclosure : Dr. Behndig has received fees from Théa Pharma GmbH as a member of the European Team for the Prophylaxis of Infection in Cataract Surgery group. Dr. Korobelnik has received consultancy fees from Alcon Surgical, Inc.; Allergan, Inc.; Alimera, Inc.; Bayer HealthCare AG; Carl Zeiss Meditec AG; Novartis Corp.; Roche Innovatis AG; and Théa Pharma GmbH.